Features of partial remission in children with type 1 diabetes using the insulin dose-adjusted A1c definition and risk factors associated with nonremission - Tsz Wai Catherine Wong; Man Yee Shirley Wong; Wai Man Betty But (Korean Society of Pediatric Endocrinology, 2021)
Purpose We sought to evaluate features of partial remission (PR) in children with type 1 diabetes mellitus (T1DM) using the insulin-dose adjusted A1c (IDAA1c) definition and to identify risk factors associated with nonremission. Methods Medical records of patients with newly diagnosed T1DM between January 1, 2008, and June 30, 2018, were retrospectively reviewed. Hemoglobin A1c (HbA1c) readings and insulin total daily doses (TDDs) of each patient at each follow-up visit were obtained with IDAA1c values calculated. PR was defined as an IDAA1c score of 9 points or less within 6 months of diagnosis. The trends of HbA1c and TDD within 2 years after diagnosis were compared between remitters and nonremitters. Factors that may predict the occurrence of PR were studied, with their relative risks of nonremission calculated. Results PR occurred in 26 patients (45.6%), including 8 girls and 18 boys, with a median duration of 8 months. The frequency of remission in male patients was significantly higher (P=0.002) and the relative risk of female sex with nonremission was 2.20 (95% confidence interval [CI], 1.24-3.91), which remained significant when adjusted by multivariate regression modeling. The initial HbA1c level at diagnosis was also significantly higher in the nonremission group (P=0.029), with a relative risk of 1.12 (95% CI, 1.01-1.25). Both HbA1c (P=0.012) and TDD (P=0.006) were significantly lower within 2 years after diagnosis among remitters than in nonremitters. TDD was significantly lower in male patients (P=0.029) during the same period, while there was no significant difference in HbA1c level between male and female patients (P=0.163). Conclusions Both the initial HbA1c level at diagnosis and sex were factors associated with the occurrence of PR. Female sex was an independent risk factor of nonremission, likely resulting from a higher insulin requirement in female T1DM patients.